PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI MAS KUI THAWALIB PUTRA PADANG PANJANG - Alwan Kurniawan (Jurnal Edukasi dan Penelitian Matematika, 2022)
Learning outcomes are the results achieved by students after carrying out learning activities and appropriate learning is truly needed in order to improving student learning outcomes. However, in reality the learning process carried out in class XI MAS KUI Thawalib Putra Padang Panjang is still not yet optimal in improving students' learning outcomes. Mathematics learning in class XI MAS KUI Thawalib Putra Padang Panjang is still on the teacher centered learning. In addition, student learning activities are still passive in learning. One of the best solutions to increase learning activities and learning outcomes are applying the Think Pair Share (TPS) learning model. TPS learning model is one of the cooperative learning models. This study purpose was describing student learning activities during the application of the TPS learning model, and describing whether mathematics learning outcomes of students in the posttest group were better than the pretest group in class XI MAS KUI Thawalib Putra Padang Panjang. This type of research is quantitative including a pre-experimental method of type one group pretest-posttest (single group initial test-end test). The instruments used are learning outcomes tests and observation sheets. Proof of research hypothesis by t test. From the data analysis, it was concluded that the activities of students who studied with the TPS model tended to increase at each meeting, and the results of learning mathematics for the sample class students in class XI MAS KUI Thawalib Putra Padang Panjang who were taught by applying the Think Pair Share learning model were different from the results. learning mathematics of students who are taught by conventional learning to the level of = 0.05.Keywords -- Cooperative Learning, Learning Activities, Learning Outcomes, Think Pair Share